Legal Responsibility of Digital Platform Companies for Protecting Shareholder Losses in The Era - Siregar, Boni; Sihotang, Lesson; Nababan, Roida (Journal of Law and Social Politics, 2025)
Background: The rapid expansion of e-commerce has driven digital platforms to integrate financial services, including stock investment features. While this innovation improves accessibility and broadens investor participation, it also generates significant legal and technological risks. Key concerns include investor protection, transparency, data security, and regulatory accountability, especially in jurisdictions like Indonesia where legal frameworks continue to evolve. The convergence of e-commerce and capital market services challenges existing regulatory structures and raises questions about platform responsibility. Objective: This study analyzes the legal responsibilities of digital platform companies in safeguarding stock investors and evaluates the adequacy of Indonesia’s regulatory framework. It further identifies regulatory gaps and proposes policy improvements to enhance investor protection. Methods: Using normative legal research with legislative and case-based approaches, this study reviews relevant laws, regulations, and judicial decisions concerning e-commerce, capital markets, and digital financial services to assess platform obligations and investor protection mechanisms. Results: Findings show that investor protection depends on adaptive regulations and consistent enforcement of platform responsibilities. Although Indonesian regulations provide basic protection, gaps persist in addressing technological risks, cross-sector integration, and platform accountability. Conclusion: Stronger regulatory harmonization, clearer liability standards, and stricter enforcement are needed. Digital platforms must enhance transparency, technological security, and investor education to mitigate risks and build trust.